(untitled) (REMUNOM, 2024)
This article explores the therapeutic potential of creatine supplementation in the prevention and treatment of frailty in the elderly through a systematic review of the scientific literature. Frailty, characterized by diminished muscle strength, endurance, and physical functionality, increases the risk of adverse outcomes such as falls, hospitalizations, and mortality among the elderly. Creatine, known for its benefits in athletic performance and muscle mass gain in the young, emerges as a promising substance for the elderly population as well, due to its ability to improve cellular energy and muscle function. The study synthesizes evidence on the effects of creatine on muscle strength, functional capacity, quality of life, and the safety of its use in elderly individuals. The findings suggest that creatine can be an effective intervention to improve the quality of life of the elderly, while also emphasizing the need for careful monitoring due to the potential for adverse effects, especially in individuals with pre-existing conditions. The review also highlights the need for further research to explore the exact mechanisms through which creatine benefits the elderly, as well as to develop clear guidelines on its dosage and administration.